Diamond growth dynamics in a constrained system - Bai, Shengyuan; Díaz, Ramón D.; Muehle, Matthias; Garratt, Elias; Baryshev, Sergey V. (Frontiers in Carbon, 2024)
Single crystal diamond (SCD) is the most promising future semiconductor. However, it has not been able to make much inroad into the microelectronics industry due to its major disadvantage of the wafer size. Among a few contender technologies, epitaxial lateral outgrowth (ELO) using microwave plasma-assisted chemical vapor deposition (MPACVD) has shown early promise toward lateral area gain during epitaxial growth. While promising, significant wafer area enhancement remains challenging. This study explores the growth dynamics of SCD in a constrained system—a pocket holder—whose effect is twofold: linear dimension and area enhancement and polycrystalline diamond (PCD) edge rim suppression. A series of pocket-type holder designs were introduced that demonstrated that the depth and substrate-to-wall distance are the major means for optimizing and enhancing lateral outgrowth while still suppressing the PCD rim. When taken together with reactor modeling, the pocket effect on the extent of ELO could be understood as directly manipulating and perturbing methyl radical flux near the growing diamond surface, thereby directly manipulating gas-to-solid phase transformation kinetics. Because it was further discovered that simple box-like pockets limit the ELO process to an exponential-decay scenario, a new generation of angled pockets was proposed that allowed boosting ELO to its fullest extent where a constant rate, linear, outgrowth was found. Our results indicate that ELO by MPACVD could become an industrial means of producing SCD at scale.